Pelatihan Teknologi Pembuatan Pupuk Organik Padat dan Rumah Kompos - Pauliz Budi Hastuti; Ngatirah Ngatirah; M. Prasanto Bimantio; Siti Tamaroh Cahyono Murti; Andreas Wahyu Krisdiarto; Gani Supriyanto (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
Organic vegetable is increasingly. It is necessary to develop organic fertilizer which can be derived from chicken manure. chicken manure is not widely used. So it is necessary to build a compost house for production of organic fertilizer. It is necessary to carry out training in making solid organic fertilizer. The beneficiaries of this community service are members of the Kenanga and Sumber Rejeki (17 participants). The method is carried out by providing a compost house, training and practice in making solid organic fertilizer. The result were the construction of a compost house and an increase in knowledge about making organic fertilizer by 24%. All of participants understood how to make organic fertilizer with a level of understanding quite understand (71%) and very understand (29 %). The solid organic fertilizer was characterized by increasing temperature and pH during the incubation, the color was black with a crumbly texture and no odor.